2001-2021, two decades of the National Theater Brigade of the MST Patativa do Assaré: resonances, challenges and interfaces with the theatrical work of Rural Education - Rafael Litvin Villas-Boas (Universidade Federal do Norte do Tocantins, 2021)
The article analyzes the experience of two decades of work by the MST National Theater Brigade in peasant communities in several Brazilian states, through the methodologies of participant observation, literature review and qualitative research. The work highlights the traditions of popular and political theater that give rise to the theatrical experience of the MST. One of the results of the research is to highlight that the peculiar dynamics of production and circulation of the Brigade had consequences in public universities, in the Degrees in Rural Education, demonstrating the potential for building a counter-hegemonic political culture.